Phenomenology and Space in Architecture: Experience, Sensation and Meaning - Saeid Soltani; Nazan Kirci (International Journal of Architectural Engineering Technology, 2019)
Until recently, architecture has been mostly evaluated over its stylistic and visual characteristics. Whereas, the architectural space is primarily vital and therefore, it should not be evaluated independently of its environment and users. Pallasmaa emphasizes on the significance of experience and connection with the environment in architecture. Phenomenology, which aims to create sensory perception, is about creating an abstract experience beyond tangibility. Sensing beyond physical entities in spatial experience deepens meaning. Buildings and cities, essentially provide the necessary view to understand and confront the human existence. It is, therefore, important for architecture to be seen as the subject of phenomenology. This paper explores the relationship between phenomenology and architectural space through experience, sensation, and meaning. It argues that the relationship between human and built environment will be strengthened to the extent that the mentioned features could participate in the space.